Rosiglitazone Inhibits Angiotensin II-Induced Proliferation of Glomerular Mesangial Cells via the Gαq/Plcβ4/TRPC Signaling Pathway - Linting Wei; Jiarong Mao; Jiamei Lu; Jie Gao; Dan Zhu; Lifang Tian; Zhao Chen; Lining Jia; Li Wang; Rongguo Fu (Cellular Physiology and Biochemistry, 2017)
Background/Aims: Mesangial cell proliferation and extracellular matrix accumulation (ECM) deposition play an important role in the pathogenesis of glomerulosclerosis. TRPC and PPAR-γ can regulate cell proliferation. Angiotensin II (AngII) can induce mesangial cell proliferation and affect TRPC expression. However, the mechanism has not been fully elucidated. This study was designed to investigate the role of TRPC and the effect of rosiglitazone (RSG) in the proliferation of rat glomerular mesangial cells (HBZY-1) that were stimulated by AngII and the underlying mechanisms. Methods: Immunofluorescence staining and qRT-PCR were performed to examine the expression levels of TRPCs in HBZY-1. Gene expression levels of TRPC, PPAR-γ, RGS4 (regulators of G protein signaling), the GPCR/Gαq/PLCβ4/TRPC signaling pathway and major downstream molecules (PCNA, SKP2, P21 and P27) were detected by qRT-PCR and western blotting. Additionally, changes in intracellular Ca2+ levels were determined through Fluo-4 Ca2+ imaging, and the cell cycle was analyzed by flow cytometry. Results: Our results found that TRPC1 and 6 were at higher expression levels in HBZY-1 cells. Following AngII stimulation, there were increased levels of TRPC1 and 6, Ca2+ entry, PCNA and SKP2, decreased expression levels of P21 and P27 and a reduced G0/G1 percentage. Silencing TRPC1 and 6 by siRNAs led to decrease in Ca2+ influx, G0/G1 cell cycle arrest and cell proliferation. Notably, PPAR-γ activation by RSG upregulated RGS4 expression, which can interact with the Gαq family to inhibit the Gαq-mediated signaling cascade. The results were similar to silencing TRPC1 and 6 by siRNAs. Conclusion: All these results indicate that RSG could inhibit HBZY-1 cell proliferation via the Gαq/PLCβ4/TRPC signaling pathway.